PENGARUH SEKTOR PARIWISATA TERHADAP PAD SUMATERA BARAT - Resti Anisa; Idris Idris; Dewi Zaini Putri (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
The study aims to determine the extent of both of simultaneous and partial influences between the number of tourist objects, tourist attractios, number of hotels and number of restaurant bussines/restaurant to local income in West Sumatera. The type of data in this study is secondary data and uses data panel from 2014-2018 from 19 Regency/City in West Sumatera. The analytical techniques used in this research are multiple linear regression. Based on the result of the test, the simultaneous number of tourist attractions, the number of tourist and the number of hotels has a significant positive impact on the original revenue of the the Regency/City in West Sumatera Province from 2014 to 2018. Meanwhile, the number of restaurant bussines/restaurant has positive impact but not significant on the original income of the Regency/City in West Sumatera Province.